Creación de una cafeteria, con la implementaciòn de materia prima y café netamente ecuatoriano, orientado a la comunidad GLBTI (gays, lesbianas, bisexuales, transexuales e intersexuales) - Tipán Tipán, Danny Patricio (2015)
Creating a coffee for a "LGBTI" group, the idea came mainly from lack of similar spaces for distraction of those people, who like all opted for open spaces, good location, service, quality and prices. The coffee is located in the sector of Reina Victoria, neighborhood known for nigh to open spaces such as restaurants, hotels, hostels and other rooms which provide food services and entertainment. It aims to offer new and classic products. The main goal is to be main stay in meeting spaces, celebrations, meetings, celebrations, etc., of a medium economy emphasizes providing the best services and atmosphere to customers; It should be noted that most gays and lesbians….